(untitled) (Medical Forum Monthly, 2024)
Objective: The study was conducted to evaluate the diagnostic accuracy of high frequency ultrasound and mammography in common breast lumps. Study Designs: Observational study Place and Duration: This study was carried at Radiology Department, LUMHS & NIMRA Jamshoro/Hyderabad and Isra University Hospital, Hyderabad from June 2008 to June 2012. Materials and Methods: A sample of 520 female of age 20 - 80 years presenting with breast lumps after initial examination were evaluated for further benignity or malignancy using ultrasonography and mammography. The findings were then compared with both diagnostic modalities. Data were entered and analyzed by using SPSS 21.0. Continuous and categorical variables were analyzed by student t test and chi square test. A p value ≤ 0.05 was considered statistically significant. Results: Mean ±SD of age was noted as 45.69 ± 10.77 years. Most of the patients were married (76.9%) and belonged to middle age group (51.5%). There were insignificant associations observed when we compared the underlying diagnosis with the diagnostic techniques used (p=0.075). On the other hand, the diagnosis in young age group was significantly made by using ultrasonography and in older group mammography was the diagnostic modality of choice (p = 0.020). Conclusion: Non-invasive test such as ultrasonography should be the preferred technique in young patients who present clinically with abreast lump.